Scandal at penn state - Crandall, William, 1956-; Parnell, John A. (John Alan), 1964-; Spillan, John E. ([London] : SAGE, 2016)
This case looks at the events surrounding the scandal of child abuse that erupted around a football coach at Penn State University. It examines the university's response in managing the crisis and asks questions of a culture that allowed abuse to carry on unchecked for so long.
Originally Published in: Crandall, W. R., Parnell, J. A., & Spillan, J. E. (2013). Scandal at Penn State. In Crisis management: Leading in the new strategy landscape (2nd ed., pp. 18-23). Los Angeles: SAGE Publications, Inc. ISBN: 9781412991681.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Pennsylvania State University; Crisis management -- Case studies